A study on various type of rotor disc brake using fae analysis - Mohd Affendi, Ibrahim (2013)
This thesis deals experiences on finding stress distribution on the various brake discs.The test is done in simulation. The disc brake is modeled using SOLIDWORK 2012software and simulation analysis is done FAE analysis using ALGOR software. Theresult for distribution stress on various disc brakes is compared. In this thesis normal,drilled, grooved and combination disc brakes are used. The result of simulation forevery type of disc brake is compared. The maximum stress von mises is simulated usingALGOR. The difference in the results between each type of disc brake is discussed. The final selected maximum stress von mises for simulation is based on mesh 100%. Force selected applied on brake pad in this simulation is 62.5 N, 125 N and 187.5 N. Simulation result maximum stress for normal disc brake is 7.544067 kN/m